Agri-environmental auctions for phosphorus load reduction : experience from a Finnish pilot - Iho, Antti; Lankoski, Jussi; Ollikainen, Markku; Puustinen, M.; Lehtimäki, Jonne (Wiley, 2014)
We examine environmental auctions on working agricultural lands. We organized a discriminatory auction where farmers were asked to make bids on spreading gypsum on their fields to reduce phosphorus loads to surface waters. The parcel-specific bids were ranked based on their load reduction–compensation ratios. To assess load reductions, we built an environmental benefit index (EBI) based on three factors: P-status of the soil (phosphorus available for crops), field slope and location with respect to waterways. As the per tonne price of gypsum delivery from the factory was higher for small quantities, the auction format allowed bundling of field parcels to reduce transportation costs. We evaluate auction's ability to target the environmental (or abatement) measures to field parcels with the highest load reduction potential and analyse the economic efficiency of the auction by comparing the pilot auction with simulated bidding behaviour and with hypothetical flat rate payment schemes. The pilot auction targeted the environmental measures effectively. It was also more efficient than a flat rate payment, even when the flat rate scheme was combined with an EBI eligibility criterion.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; tarjouskilpailu maatalouden ympäristönsuojelussa; ympäristöhyötyindeksi; environmental benefit index; information rent; phosphorus load; pilot; fosforikuorma; fosfori; ympäristönsuojelu; maatalous; auctions; phosphorus; tarjouskilpailu